Концепция сетецентрического управления посадкой самолетов по свободным траекториям с технологией решения конфликтных ситуаций - Павлов, В.В.; Волошенюк, Д.А.; Волков, А.Е. (Кибернетика и вычислительная техника, 2014)
Рассмотрен вопрос необходимости создания комплексной системы управления посадкой самолетов по свободным траекториям, основанной на принципах эргатичности и сетецентричности и учитывающей возможные конфликтные ситуации самолетов в воздухе с целью их предупреждения или разрешения. Задачей системы станет повышение безопасности авиационных перевозок, решение части экологических и экономических проблем, решение проблемы перегруженности аэропортов по причине возрастающей интенсивности воздушного движения. Розглянуто питання необхідності створення комплексної системи керування посадкою літаків за вільними траєкторіями, заснованої на принципах ергатичності та мережецентричності з врахуванням можливих конфліктних ситуацій літаків в повітрі, з метою попередження або вирішення цих ситуацій. Завданням системи стане підвищення безпеки авіаційних перевезень, вирішення частини екологічних та економічних проблем, вирішення проблеми перевантаженості аеропортів з причини зростаючої інтенсивності повітряного руху. Purpose: The creation of a network-centric control system for planes landing at free path with regard to the factors of conflict situations. Results: The development and the use of aircraft are directly related to modeling in those areas where information systems are complex. In addition, the simulation is a major step in system analysis. So, of course, there are modern information technologies that provide automation of this process. However, it should be noted that the specific main task that stands before us now is not normal flight simulation aircraft and its flight simulations under difficult circumstances, conflicts, threats to the collision at take-off and landing phases. That is, those flight conditions when the danger is at its highest level and taking into account the human factor may be a threat of disaster.